Pisolithus arhizus (Scop.) Rauschert improves growth of adventitious roots and acclimatization of in vitro regenerated plantlets of Pinus pinea L. - Ragonezi, C. (2012)
Stone pine (Pinus pinea L.) is an economically important forest tree in the Mediterranean region and has been the target of breeding and selection through micropropagation mainly for its ecological and ornamental aspects. A crucial step in micropropagation is adventitious rooting of microshoots, which often is highly inefficient in most conifer species including stone pine. Hence, we conducted in vitro co-culture of Pinus pinea microshoots with the ectomycorrhizal fungus Pisolithus arhizus (isolated from natural stands) in order to promote adventitious root growth and plant survival during acclimatization. Significant differences were found in the number of branches, in the number of roots plus branches, in total length of roots, in total length of roots plus branches, in average root length and in the length of the longest root in inoculated plants during in vitro rooting compared with non-inoculated plants. The roots of inoculated plants also grew better in vermiculite and during acclimatization in a mixed substrate compared with roots of control plants resulting in the development of vigorous root system. Overall, mycorrhizal inoculation increased the survival rate of the regenerated pine.